Regulation of Skeletal Muscle Plasticity by Protein Arginine Methyltransferases and Their Potential Roles in Neuromuscular Disorders - Stouth, Derek W.; vanLieshout, Tiffany L.; Shen, Nicole Y.; Ljubicic, Vladimir (Frontiers in Physiology, 2017)
Protein arginine methyltransferases (PRMTs) are a family of enzymes that catalyze the methylation of arginine residues on target proteins, thereby mediating a diverse set of intracellular functions that are indispensable for survival. Indeed, full-body knockouts of specific PRMTs are lethal and PRMT dysregulation has been implicated in the most prevalent chronic disorders, such as cancers and cardiovascular disease. PRMTs are now emerging as important mediators of skeletal muscle phenotype and plasticity. Since their first description in muscle in 2002, a number of studies employing wide varieties of experimental models support the hypothesis that PRMTs regulate multiple aspects of skeletal muscle biology, including development and regeneration, glucose metabolism, as well as oxidative metabolism. Furthermore, investigations in non-muscle cell types strongly suggest that proteins such as peroxisome proliferator-activated receptor-γ coactivator-1α, E2F transcription factor 1, receptor interacting protein 140, and the tumor suppressor protein p53, are putative downstream targets of PRMTs that regulate muscle phenotype determination and remodelling. Recent studies demonstrating that PRMT function is dysregulated in Duchenne muscular dystrophy, spinal muscular atrophy, and amyotrophic lateral sclerosis suggests that altering PRMT expression and/or activity may have therapeutic value for neuromuscular disorders. This review summarizes our understanding of PRMT biology in skeletal muscle, and identifies uncharted areas that warrant further investigation in this rapidly expanding field of research.